Aplikasi Akuntansi “Friendly” untuk Mengatasi Masalah Penysunan Laporan Keuangan BUMDes - I Made Wianto Putra; I Wayan Kartana; I Gede Aryawan; Miswaty Miswaty (Abdimas Universal, 2022)
The ownership of village institutions is jointly controlled with the aim of improving the community's economic standard of living, one of which is through Village Owned Enterprises (BUMDes). BUMDes partners in Selulung Village and Belantih Village face obstacles with the implementation of bookkeeping or accounting. The partner problems, are: (1) Due to the lack of knowledge in recording transactions and preparing financial statements, (2) There is no partner awareness to fix financial management so that it can solve financial problems, (3) Partners do not have the knowledge of financial management about how to separate business finances from personal (household) finances. The solutions offered related to problem solving for BUMDes partners are: (1) Provide counseling activities regarding the importance of orderly administration in running BUMDes business, (2) Provide training activities for preparing financial reports with accounting applications namely “Friendly”. Analysis through the distribution of questionnaires to participants to obtain an overview related to the benefits of the training seen from the material got score 4.67 which was close to very good, the delivery of material with score 4.53 was also almost very good, the application made a score of 5 was very good. Until now, improvements and application trials are continuously being carried out so that they can be directly applied to each BUMDes.